MODAL INISIASI INDIKATOR KINERJA FINANSIAL - Hudiyanto, . (Jurnal Ekonomi & Studi Pembangunan, 2010)
The effectiveness of the policies of poverty reduction in the region of the poor and the excluded are always limited by the ironic fact. On the one hand, there is an outflow of assets from village to an area outside the village in the form of savings, skilled resources, human resources, social capital, and political capital, while on the other hand the availability of funds to survive in the area is relatively small. It rises what is called a negative inflow. To overcome the problem of poverty in communities experiencing negative inflow, it neededmodel of economic development approach based on the potential to utilize local assets. Solving the problem with relying on external parties (banks, government agencies, commercial) can no longer expect much. This study attempts to reveal the potential and the possibility of development of financial institutions "from, for, and by community". This study aimed to identify not only financial capital but also social capital and political capital possessed by thesociety to overcome the problems they face. This research was conducted to identify not only financial capital but also social capital and political capital possessed by the people to overcome their problems.